2023
DOI: 10.1101/2023.08.31.555664
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Dark taxonomy”: a new protocol for overcoming the taxonomic impediments for dark taxa and broadening the taxon base for biodiversity assessment

Rudolf Meier,
Amrita Srivathsan,
Sarah Siqueira Oliveira
et al.

Abstract: We are entering the 6th mass extinction event on the planet with scarcely any data for "dark taxa" that comprise most animal species. These taxa have been neglected, because conventional taxonomic methods are not well-equipped to process tens of thousands of specimens belonging to thousands of species. We here test a new protocol for tackling this data deficiency problem by simultaneously addressing (1) taxonomic impediments, (2) lack of biodiversity baseline data, (3) and low impact of revisionary research. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 121 publications
0
3
0
Order By: Relevance
“…Barcodes were obtained for all specimens, but the targeted morphological checks only required revisiting just over 5% of specimens. A second successful validation of LIT was recently undertaken by Meier et al [37] for 1456 specimens of Mycetophilidae (Diptera) which were shown to contain 120 species based on a LIT analysis. Compared to the first test based on phorid flies, a larger proportion of specimens had to be checked for MOTU validation because studying only one specimen for each of the 120 species already meant inspecting greater than 8% of all specimens in the sample (n = 1456).…”
Section: From Megabarcoding To Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Barcodes were obtained for all specimens, but the targeted morphological checks only required revisiting just over 5% of specimens. A second successful validation of LIT was recently undertaken by Meier et al [37] for 1456 specimens of Mycetophilidae (Diptera) which were shown to contain 120 species based on a LIT analysis. Compared to the first test based on phorid flies, a larger proportion of specimens had to be checked for MOTU validation because studying only one specimen for each of the 120 species already meant inspecting greater than 8% of all specimens in the sample (n = 1456).…”
Section: From Megabarcoding To Speciesmentioning
confidence: 99%
“…Compared to the first test based on phorid flies, a larger proportion of specimens had to be checked for MOTU validation because studying only one specimen for each of the 120 species already meant inspecting greater than 8% of all specimens in the sample ( n = 1456). Still, LIT was again found to be effective at resolving conflict between MOTUs and morphology by studying the morphology of only a small subset of all specimens [ 37 , 38 ].…”
Section: From Megabarcoding To Speciesmentioning
confidence: 99%
See 1 more Smart Citation